Highly refractive polyimides containing pyridine and sulfur units: synthesis and thermal, mechanical, solubility and optical properties. Issue 7 (3rd April 2017) - Guan, Yue; Dong, Weibing; Wang, Che; Shang, Dejing
Abstract: Two series of isomers containing pyridine and sulfur unit aromatic diamine monomers, 4, 4′‐bis(5‐amino‐2‐pyridinylsulfanyl)diphenyl sulfide (2a ), 4, 4′‐bis(6‐amino‐3‐pyridinylsulfanyl)diphenyl sulfide (2b ) and 4, 4′‐bis(5‐amino‐6‐methyl‐2‐pyridinylsulfanyl)diphenyl sulfide (2c ), 4, 4′‐bis(5‐amino‐4‐methyl‐2‐pyridinylsulfanyl)diphenyl sulfide (2d ), were designed and synthesized. Aimed at clarifying the structure–property relationships of pyridine‐ and sulfur‐containing high refractive polymers, 2a was polymerized with various dianhydrides to prepare polyimides PI‐1−PI‐7 and2b, 2c, 2d were reacted with 4, 4′‐[ p ‐thiobis(phenylenesulfanyl)]diphthalic anhydride to prepare polyimides PI‐8−PI‐10. The polyimides showed excellent optical properties with average refractive indices ranging from 1.7006 to 1.7620 and birefringence as low as 0.0056. Meanwhile, comparative studies on their properties including solubility, thermal and mechanical, and optical transparency properties were performed. Some property differences of the isomers caused by the sequence changes were found. © 2017 Society of Chemical Industry Abstract : Systematic research was carried out on the properties of PI‐1−PI‐7 derived from diamine (2a ) and aromatic dianhydrides. Meanwhile, PI‐8 (2b /3SDEA), PI‐9 (2c /3SDEA) and PI‐10 (2d /3SDEA) were prepared for investigating the structure–property relations of isomeric polyimides. The pyridine‐ and thioether‐containing polyimides showed high refractive indices and excellent optical transparency.